PENGEMASAN VAKUM PADA GURAMI PRESTO UNTUK MENINGKATKAN KUALITAS PRODUK DI KOPERASI PRODUKSI AMANAH SEJATI KOTA BENGKULU - Ulfah Anis; Mimi Sutrawati (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Gourami fish has been cultivated and marketed by the Amanah Sejati cooperative located in Bengkulu city. Gurami is sold as fresh product. The price is not comparable with the cost of gurami cultivation. Therefore, it is necessary to make an effort to increase the economic value of the gourami fish. One of the solutions is to make it into presto gourami products. The gourami fish is then vacuum-packed to improve the quality and extend its shelf life. Community service aims to (1) provide knowledge about the type of packages, and (2) provide knowledge about how to vacuum packaging on presto gourami. These community services are coordination and socialization, counseling, and practice. These services were going well. The participants were enthusiastic about the counseling and practice.